Assisted Dying & Disability. (17th April 2017) - Riddle, Christopher A.
Abstract: This article explores at least two dominant critiques of assisted dying from a disability rights perspective. In spite of these critiques, I conclude that assisted dying ought to be permissible. I arrive at the conclusion that if we respect and value people with disabilities, we ought to permit assisted dying. I do so in the following manner. First, I examine recent changes in legislation that have occurred since the Royal Society of Canada Expert Panel on End‐of‐Life Decision‐Making report, published in this journal. I suggest that these changes are likely to only strengthen opposition to assisted dying from disability rights activists and people with disabilities. Second, I focus on respect for people with disabilities and in particular, respect for their autonomy and decision‐making abilities. Third, I explore the opposition to assisted dying that focuses on risk and the vulnerability of people with disabilities. Here I suggest that this risk ought not to be of special concern. Ultimately, I conclude that upholding respect for the disabled requires the legalization of assisted dying, rather than the denial of access in a misguided effort to protect people with disabilities.